The Synergy of Work Allowances, Sports Facilities, and Motivation in Enhancing Athlete Achievement - Qomariah, Nurul; Suryandari, Andriana; Martini, Ni Nyoman Putu; Sari, Mutiara Dwi (Universitas Brawijaya, Indonesia, 2024)
In the era of globalization, athlete achievement is very important for a country or sports institution, whether in the form of medals, records, or positions in championships, which are also measured by increasing achievement. It is important for institutions or organizations to be able to maintain the achievements of athletes that have been achieved. This study has the following objectives: determine the impact of work allowances and sports facilities on motivation and athlete achievement under the auspices of the Jember Regency Youth and Sports Office. The population in this study was 399 athletes from 35 sports branches in the Jember Regency Dispora. The number of samples was determined by as many as 150 respondents. Data analysis used SEM with WarpPLS 7.0. The results of this study indicate that the work allowance variable has a positive and significant effect on motivation. The sports facility variable has a positive effect on motivation but is not significant. The work allowances variable does not have a significant effect on athlete achievement. The sports facilities variable has a positive and significant effect on athlete achievement. The motivation variable has a positive and significant effect on the achievement of athletes from the Jember Regency Diaspora. The work allowances variable has a positive and significant effect on the achievement of athletes from the Jember Regency Dispora through motivation. The sports facilities variable has a positive effect on the athlete achievement of athletes from Jember Regency through motivation. The practical implications that can be contributed from this study are that sports facilities do not affect motivation but do affect achievement. Work allowances contribute to motivation but do not affect athlete achievement. Therefore, sports facilities must improve their benefits for motivation to achieve more. Work allowances also need to be improved so that athlete retention increases.